On-sky Closed-loop Correction of Atmospheric Dispersion for High-contrast Coronagraphy and Astrometry. (15th January 2018) - Pathak, P.; Guyon, O.; Jovanovic, N.; Lozi, J.; Martinache, F.; Minowa, Y.; Kudo, T.; Kotani, T.; Takami, H.
Abstract: Adaptive optic (AO) systems delivering high levels of wavefront correction are now common at observatories. One of the main limitations to image quality after wavefront correction comes from atmospheric refraction. An atmospheric dispersion compensator (ADC) is employed to correct for atmospheric refraction. The correction is applied based on a look-up table consisting of dispersion values as a function of telescope elevation angle. The look-up table-based correction of atmospheric dispersion results in imperfect compensation leading to the presence of residual dispersion in the point spread function (PSF) and is insufficient when sub-milliarcsecond precision is required. The presence of residual dispersion can limit the achievable contrast while employing high-performance coronagraphs or can compromise high-precision astrometric measurements. In this paper, we present the first on-sky closed-loop correction of atmospheric dispersion by directly using science path images. The concept behind the measurement of dispersion utilizes the chromatic scaling of focal plane speckles. An adaptive speckle grid generated with a deformable mirror (DM) that has a sufficiently large number of actuators is used to accurately measure the residual dispersion and subsequently correct it by driving the ADC. We have demonstrated with the Subaru Coronagraphic Extreme AO (SCExAO) system on-sky closed-loop correction of residual dispersion to <1 mas across H-band. This work will aid in the direct detection of habitable exoplanets with upcoming extremely large telescopes (ELTs) and also provide a diagnostic tool to test the performance of instruments which require sub-milliarcsecond correction.